Lagged effect of Patient‐Reported Outcomes Measurement Information System (PROMIS) Sleep Disturbance on subacute postsurgical PROMIS Pain Behavior. Issue 4 (21st July 2022) - Highland, Krista B.; Parry, James; Kent, Michael; Patzkowski, Jeanne C.; Patzkowski, Michael S.; Herrera, Germaine; Kane, Alexandra; Giordano, Nicholas A.
Abstract: Sleep disturbance is a modifiable risk factor that, when reduced, may improve subacute postsurgical outcomes (e.g., pain‐related impact). Evidence also indicates that pain and sleep may have a bidirectional longitudinal relationship before to (sub) acutely after surgery. The objective of the present study is to examine the degree to which sleep disturbances and pain behavior have uni‐ or bidirectional relationships in a sample of patients undergoing sports orthopedic surgery. In this observational, longitudinal cohort study, participants ( = 296) were adult (ages 18+) active duty service members who underwent open or arthroscopic shoulder or knee surgery at Walter Reed National Military Medical Center. Participants were asked to complete PROMIS Sleep Disturbance and Pain Behavior computer adaptive testing item banks before surgery, 6 weeks postsurgery, and 3 months postsurgery. Patient‐level covariates were analyzed for interrelationships using nonparametric bivariate statistics. Autoregressive and cross‐lagged structural equation modeling examined the bidirectional relationships of patient‐level covariates and PROMIS outcomes. When controlling for patient‐level covariates, sleep disturbance at presurgical and 2‐week postsurgical timepoints were positively associated with both sleep disturbance and pain behavior at the subsequent timepoint. Sleep disturbance may contribute to pain‐related functioning and quality of life after sports orthopedic surgery. Future studies utilizing multidimensional patient report outcomes and robust analytics are needed to better understand whether sleep‐targeted interventions can improve subacute and long‐term orthopedic sports surgery outcomes.